A new dual stainless steel cryogenic trap for efficient separation of krypton from argon and xenon. Issue 11 (23rd September 2020) - Péron, Sandrine; Mukhopadhyay, Sujoy; Huh, Michael
Abstract : We use a new cryogenic system and a new protocol to achieve efficient krypton separation from argon and xenon. Abstract : The elemental and isotopic abundances of krypton and xenon provide critical insights into processes ranging from stellar nucleosynthesis to volatile accretion and paleotemperatures on Earth. Accurate and precise determination of the krypton and xenon elemental abundance and isotopic ratios requires sample purification and noble gas separation to avoid interferences in the mass spectrometer. However, effective separation of krypton (Kr) from argon (Ar) and xenon (Xe) has remained challenging. Here, we present a new cryogenic instrument associated with a new protocol to achieve an efficient and effective separation of Kr from Ar and Xe. Using two electropolished stainless steel cryogenic traps on a single cold head, distillation of the noble gases from one trap onto the other and temperature cycling of the traps to reduce the effect of cryotrapping allows ≥98% of the Kr in a sample to be recovered with <0.5% of the Ar and <1% of the Xe abundances of the sample. Likewise, more than 99% of the Xe fraction can be recovered with <1% Kr. No variations in the isotopic ratios of the separated Kr and Xe fractions are observed as a function of the signal size for air standards. Moreover, we find that krypton isotopes can be fractionated during Ar–Kr separation. We suggest that more accurate krypton isotopic compositions can be obtained by maximizing the recovered krypton fraction instead of minimizing the argon fraction within krypton.